Firm Value Reviewing from Debt Policy, Dividend Policy and Ownership Structure - Adra Mutama; Zefriyenni; Sigit Sanjaya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2021)
This study aims to determine the extent to which firm value is influenced by the company's dividend policy and ownership structure. The research population is property and real estate companies listed on the Indonesia Stock Exchange for the period 2014-2018, totaling 70 companies. The sample was determined by purposive sampling method, the number of research samples is 20 companies. Data analysis used the estimation model test, classical assumption test, panel data regression, hypothesis testing consisting of the F test and t test. The results showed that: (a) debt policy partially has a positive and significant effect on firm value (b) dividend policy partially has a positive and significant effect on firm value. (c) institutional ownership has a positive and significant effect on firm value. (d) managerial ownership partially has a positive and significant effect on firm value.